Ataxic sensory neuronopathy with isolated anti-Ro/SS-A antibody during pregnancy: a case report of adverse outcomes - Smaili, Rachid; Ferjouchia, Zahra; Elbachiri, Soumaya; Bourkia, Myriem (Frontiers in Lupus, 2024)
We present the rare case of a 33-year-old pregnant woman who developed severe ataxic sensory neuronopathy associated with isolated anti-Ro/SS-A antibodies without other features of Sjögren's syndrome. Her symptoms, which began with numbness and paresthesia, progressed to severe ataxia and sensory impairment, complicated by preeclampsia and intrauterine fetal death. Despite treatment with intravenous immunoglobulin, azathioprine, and steroids, she remains disabled. This case raises awareness for anti-Ro/SS-A antibodies in pregnant women and underscores the importance of early intervention and a multidisciplinary approach to prevent severe neurological disability.